Sympathetic activity markers in patients with resistant hypertension with renal dysfunction - S. A. Afanasyev; A. A. Popova; T. Yu. Rebrova; M. A. Manukyan; V. A. Lichikaki; N. I. Ryumshina; E. F. Muslimova; I. V. Zyubanova; E. I. Solonskaya; S. A. Khunkhinova; I. А. Skomkina; V. F. Mordovin; et al. (Кардиоваскулярная терапия и профилактика)
Aim. To study the informativeness of sympathetic activity markers and perirenal adipose tissue (PRAT) in assessing renal function decline in patients with resistant hypertension (RH).Material and methods. The study included 63 patients with RH of both sexes aged 40-80 years. The main group included 19 patients with chronic kidney disease (CKD). The control group consisted of 44 patients with RH without CKD. All patients were assessed for uric acid, blood lipid profile, beta-adrenergic reactivity of erythrocyte membranes, free metanephrine and normetanephrine in plasma and 24-hour urine. The renal function was assessed by the glomerular filtration rate calculated using the CKD-EPI equation. Twenty-four hour blood pressure monitoring was performed on the brachial artery of one arm at intervals of 15 minutes during the day and 30 minutes at night. Kidney size and PRAT were calculated based on the magnetic resonance imaging.Results. In both groups of patients, a significant increase in blood normetanephrine and beta-adrenergic reactivity of erythrocyte membranes relative to the reference values was shown. Blood and 24-hour urine metanephrine were within the reference intervals. No differences were found between the sympathetic activity indices in the main and control groups. In the main group patients, the PRAT thickness was greater (p=0,013), and the kidney diameter was smaller (p=0,046) than in the control group patients.Conclusion. CKD in RH patients is not accompanied by additional significant changes in sympathetic regulation, assessed by the blood and 24-hour urine catecholamine levels, the degree of beta-adrenergic receptor desensitization and variability of blood pressure. PRAT increase according to magnetic resonance imaging in patients with RH is associated with a decrease in renal filtration function.